Temporal sequence of geodynamic development processes in the territory of Ukraine from the Eoarchean to Anthropogen - O.B. Gintov (Геофизический журнал, 2017)
Survey data of geodynamic studies, completed during the latest 20 years in Ukraine for most of its regions, have been generalized in order to summarize the results of regional studies into geo-historical line from Eoarchean to Anthropogen. For this purpose the data of stratigraphy and isotopic geochronology obtained by Ukrainian and foreign scientists within the studied territory have been used in the work. It has been shown that the basic role in contemporary concepts on the character of geodynamic processes within the territory of Ukraine is played by the results of thorough studies of deep structure of the crust and mantle, fulfilled by the Institute of Geophysics NAS of Ukraine at the high methodic level with participation of many international organizations. Methods of seismometry and seismotomography, gravimetry and magnitometry, geothermic and deep electrometry as well as paleomagnetic and tectonophysical data were actively used. The data obtained show that geodynamic processes based on plate tectonics mechanisms arc clearly manifested in the studied territory since Neoarchean. For Eoarchcan and Mesoarchean plum-tectonic mechanisms are more probably specific. Present-day structure of the shield was definitely formed between 1,8 and 1,7 Ga isochronously with formation of the micro- continent Sarmatia, its affiliation with Fennoscandia and Volgo-Uralia into the continent Baltics on the background of the supercontinent Pangea-1. Geodynamic processes in Meso-Proterozoic and Early Paleozoic are examined in discussion form and it has been shown that up to Middle Devonian they were mainly concentrated in the western part of Ukraine in the territory of the present-day Carpathians and Volyn-Podolian plate. These processes were manifested as formation of Volyn-Polessian flexure (Middle Riphean), Galitsian-Belostok basin (Late Riphean), which joined the oceans Proto-Tethys and Proto-Yapetus westward of Baltic, formation in its place of orogen of Pre-Carpathians (Vendian), formation of the Dnister pericraton and (Upper Vendian) which finishes in the southwest by Pre-Galitsian foothills, TESZ zone and the Thornquist sea. Independent study of Vendian deposits of Ukraine by paleomagnetic and tectonophysical methods has shown that at this period virtual rotation axis of the Earth was sub-parallel to present-day latitudes. Activation of geodynamic processes in the remaining territory of Ukraine began in the Devonian after formation of supcrcontinent Euro-America: formation of the Donbass branch of the ocean Paleotethys and the Prypiat-Dnieper-Donets riftogen with possible sub- oceanic crust (Upper Devonian); separation of Misian, Scythian and Turanian microplates from East-European platform and their transformation into terrains of Paleotethys; affiliation of Gondvana with Lavrasia and formation of the supercontinent Pangaea (the Permian-Triassic). Paleomagnetic studies of the Permian and Triassic dyke complexes of the western part of the Ukrainian Shield allowed to make a choice between two models of Pangaea (A and B) and to prefer the model A (vengerovskaya). In Mesozoic-Cenozoic active geodynamic processes were concentrated in the Alpine margin of the East-European platform; formation of the Mesotethys ocean and its western part Alpine Tethys (Middle Triassic); opening of the Taurean basin (Middle Triassic—Early Jurassic), its closure and formation of folding of Taurean series of rocks in North Dobrogea and West Crimea (Middle Jurassic); the opening of the West Black Sea (Upper Cretaceous) and East Black Sea (Eocene) basins; closure of the oceans of the Alpine Tethys, westward movement of micro-plates Alcapa and Tissia-Dakia and formation of the arc of the Carpathian orogen (Upper Cretaceous-Neogene); collision process in the Crimean—Black Sea region in the variant of two-layered plate tectonics and the uplift of the Mountain Crimea (Pliocene—present-day). The data resulted show that the mechanisms of paleo- and present-day geodynamics — plate tectonics and plum-tectonics explain appropriately enough all geological and geophysical phenomena observed in nature, especially those ones which were revealed during the second part of the 20th — and 21st centuries.